Optical and magnetic properties of Ni-implanted and post-annealed ZnO thin films - OKAY, CENGİZ (SPRINGER HEIDELBERG, 2011)
Single-crystalline ZnO thin films have been grown on sapphire substrates and implanted by 40 keV Ni+ ions with a dose of 0.25-1.25x10(17) ions/cm(2). After implantation the samples have been annealed at T=1000A degrees C for 30 minutes in air. Both as-prepared and annealed nickel-implanted ZnO samples have been investigated by ferromagnetic resonance (FMR), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM), and optical techniques. SEM studies reveal that the surface of non-implanted ZnO thin film is very smooth, while microcracks are present in the Ni-implanted ZnO samples. Annealing after implantation recovers the surface of the implanted ZnO. Energy dispersive X-ray spectroscopy shows that the Ni concentration increases with increasing the implantation dose. Optical measurements of the Ni-implanted ZnO thin films indicate that annealing results in formation of a new phase. This phase is attributed to NiO that appears due to redistribution and oxidation of the implanted Ni ions in the ZnO matrix. Magnetic measurements show that both as-implanted and annealed samples exhibit room-temperature ferromagnetism. VSM data indicate that annealing procedure results in decreasing the magnetic moment per Ni atom and higher coercivity at low temperatures. Magnetic-resonance studies reveal highly anisotropic FMR signal in the as-implanted Ni:ZnO samples starting from the dose of 0.5x10(17) ions/cm(2). We also observe a step-wise increase of the effective magnetization at the dose of 1.0x10(17) ions/cm(2), which is explained by magnetic percolation of the Ni nanoparticles. Narrow resonance signals with unusual angular dependence are observed in magnetic-resonance studies of the annealed Ni:ZnO samples, which have been related to the formation of a system of non-percolated NiO-coated Ni nanoparticles as a result of annealing in air. We did not observe experimental evidence for intrinsic ferromagnetism in the Ni-implanted ZnO thin films.
Keywords: ROOM-TEMPERATURE FERROMAGNETISM; DOPED ZNO; ANISOTROPY; COBALT; TIO2